2022
DOI: 10.1111/apt.16806
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: development of a consensus code set to identify cirrhosis in electronic health records

Abstract: Background: Electronic health records (EHRs) collate longitudinal data that can be used to facilitate large-scale research in patients with cirrhosis. However, there is no consensus code set to define the presence of cirrhosis in EHR. This systematic review aims to evaluate the validity of diagnostic coding in cirrhosis and to synthesise a comprehensive set of ICD-10 codes for future EHR research.Method: MEDLINE and EMBASE databases were searched for studies that used EHR to identify cirrhosis and cirrhosis-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…The incidence of claims was calculated for people with cirrhosis and liver transplantation. This was accomplished by searching the electronic medical records for patients with validated diagnosis codes for cirrhosis 7 and for all patients who had received or undergone a liver transplant. We could not determine a denominator for CLD as many (eg, NAFLD, alcohol-associated liver disease) have insensitive diagnostic codes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of claims was calculated for people with cirrhosis and liver transplantation. This was accomplished by searching the electronic medical records for patients with validated diagnosis codes for cirrhosis 7 and for all patients who had received or undergone a liver transplant. We could not determine a denominator for CLD as many (eg, NAFLD, alcohol-associated liver disease) have insensitive diagnostic codes.…”
Section: Methodsmentioning
confidence: 99%
“…We rendered all CLDs and cirrhosis complications into validated diagnostic codes 7 to pull closed cases attributed to those diagnostic codes from Candello’s Comparative Benchmarking System. (Supplementary Table 1, http://links.lww.com/HC9/A247 ) Candello is a division of the Risk Management Foundation and the Controlled Risk Insurance Company.…”
Section: Methodsmentioning
confidence: 99%
“…Algorithms that use a combination of ICD codes, or a combination of ICD codes and laboratory results, could improve diagnostic accuracy 36 , 113 , 115 , 122 . One systematic review has identified nine ICD-10 codes that have been used to identify cirrhosis most frequently in the literature 118 . When validated in Europe and North America, this set of nine ICD-10 codes had greater sensitivity than the code set most frequently used in the literature 121 , and maintained a high positive predictive value (83–89%).…”
Section: Trends In the Aetiology Of Cirrhosismentioning
confidence: 99%
“…When validated in Europe and North America, this set of nine ICD-10 codes had greater sensitivity than the code set most frequently used in the literature 121 , and maintained a high positive predictive value (83–89%). This consensus code set could, therefore, be a useful tool for identification of cirrhosis in large databases and health records, and should be further validated in regions outside North America and Europe 118 .…”
Section: Trends In the Aetiology Of Cirrhosismentioning
confidence: 99%
“…Additional comorbidity covariates included diagnoses for cirrhosis, hepatitis B virus infection, hepatitis C virus infection, and alcohol-related diseases. These diagnoses were considered for the period of time from one year before cancer diagnosis to six months after diagnosis [39][40][41].…”
Section: Plos Onementioning
confidence: 99%